Nuclear localization of MUC1 extracellular domain in breast, head and neck, and colon cancer - Rabassa, Martín Enrique (2015)
Background: The glycoprotein MUC1 is overexpressed and underglycosylated in cancer cells. MUC1 is translated as a single polypeptide that undergoes autocleavage into 2 subunits (the extracellular domain and the cytoplasmic tail), and forms a stable heterodimer at the apical membrane of normal epithelial cells. The MUC1 cytoplasmic tail localizes to the cytoplasm of transformed cells and is targeted to the nucleus. Aims: To study the expression of the MUC1 extracellular subunit in cell nuclei of neoplastic breast, head and neck, and colon samples. Materials and Methods: 330 primary tumor samples were analyzed: 166 invasive breast carcinomas, 127 head and neck tumors, and 47 colon tumors; 10 benign breast disease (BBD) and 40 normal specimens were also included. A standard immunohistochemical method with antigen retrieval was performed. Nuclear fractions from tissue homogenates and breast cancer cell lines (ZR-75, MDA-MB-231, MCF7, and T47D) were obtained and analyzed by Western blotting (WB). The anti-MUC1 extracellular subunit monoclonal antibody HMFG1 was used for immunohistochemistry. Results: 37/166 breast cancer specimens, 5/127 head and neck cancer specimens, 2/47 colon cancer samples, and 3/10 BBD samples showed immunohistochemical staining at the nuclear level. No nuclear reaction was detected in normal samples. By WB, breast and colon cancer purified nuclear fractions showed reactivity at 200 kDa in 3/30 breast and 3/20 colon cancer samples as well as purified nuclear fractions obtained from breast cancer cell lines. Conclusions: This study shows that the MUC1 extracellular domain might be translocated to the cell nucleus in breast, head and neck, and colon cancer as well as BBD.